Meningkatkan Karakter Anak Usia Dini Menjadi Mandiri Sentra Bahan Alam di PAUD Negeri Percontohan - Nasution, Zahra Ayuni; Daulay, Nurussakinah (EduInovasi: Journal of Basic Educational Studies, 2024)
The study's title is "Improving the Character of Early Childhood Students to Become Independent Natural Material Centres in Pilot State Early Childhood Education" . The purpose of this study is to learn how to help youngsters in Pilot State PAUD's natural resource centres develop strong moral fibre and self-reliance. This study employs a qualitative strategy, namely an action research strategy used in a classroom setting over the course of two cycles. The phases of preparation, execution, and evaluation are repeated in each cycle. Ten children, five boys and five girls, ages five and six from group B in the Pilot State PAUD were observed, together with their instructors, as part of the data collection process. This study found that eight out of ten children (80%) in Cycle II were judged to have "developed very well" (BSB) or "developed according to expectations" (BSH). Specifically, the activity "Making screen printing collages using leaves" teaches kids to appreciate the process and outcome of play with natural materials. Children can develop their own sense of independence, bravery, and responsibility via the use of learning activities made from natural resources.